Respuesta :
You group the like terms and multiply, and remember that when you multiply two like terms like x^4 times x^3 you ADD the exponents, so you would have x^7.
For this problem:
so for the x's: -3x^2(4x^3) = -12x^5;
now for the y's: y^2(y^4) = y^6;
so your final answer is -12x^5y^6
For this problem:
so for the x's: -3x^2(4x^3) = -12x^5;
now for the y's: y^2(y^4) = y^6;
so your final answer is -12x^5y^6
Answer:
-3x^5y^6
Step-by-step explanation:
-3x^2y^2*y^4x^3
x^3x^2=x^2+3=x^5= -3x^5y^4y^2
Y^4y^2=Y^2+4=Y^6= -3x^5y^6